Effects of Interest Rate and Exchange Rate on Volatility of Market Index at Dhaka Stock Exchange - Muktadir-al-Mukit, Dewan (Journal of Business and Technology (Dhaka), 2013)
The paper investigates the effects of the exchange rates and interest rates on stock market performance by using monthly time series data for the economy of Bangladesh, over the period of 1997 to 2010. This study uses econometric techniques of measuring the long and short term relationship between variables using the concept of Cointegration and Error Correction Model and analysis of Variance Decomposition. Causal relationships have been investigated using Granger causality test. By employing Cointegration technique it is observed that in the long run, a one percent increase in exchange rate and in interest rate contributes1.04% increase and 1.71 % decrease in market index respectively. The estimated error correction coefficient indicates that 7.8 percent deviation of stock returns are corrected in the short run. Finally, Granger causality analysis suggests the existence of a unidirectional causality from market index to exchange rate and from interest rate to market index. DOI: http://dx.doi.org/10.3329/jbt.v7i2.16451 Journal of Business and Technology Vol.7(2) 2012: 1-18